2023
DOI: 10.31219/osf.io/ny2rc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineering of crop plants to facilitate bottom-up innovation: A possible role for broad host-range nitroplasts and neoplasts

Abstract: The astonishing gains in agricultural output since the 1960's has come at an environmental cost. It has also failed to bring much benefit to sub-Saharan Africa, the region of the world that is predicted to have the greatest population increase in the coming decades and greatest agricultural need. The increase in productivity required to feed the billions that will soon be added to the world's population is more likely to succeed if creative direction lies in the hands of those most intimately acquainted with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 438 publications
0
2
0
Order By: Relevance
“…Although it has been suggested that there is no reason why an N 2 -fixing organelle could not be maintained in the cell, such organelles have yet to be described ( 51 ). The findings of this study, along with the regulation of spheroid body size ( 17 ) and coevolution of B. bigelowii and UCYN-A ( 53 ), suggest that the evolution of the nitroplast is underway and establish B. bigelowii as an important model system of great interest for understanding organellogenesis, with implications for contemporary efforts to engineer N 2 -fixing capabilities into agricultural plants ( 10 , 57 ).…”
Section: Ucyn-a As a Nitrogen-fixing Organellementioning
confidence: 81%
See 1 more Smart Citation
“…Although it has been suggested that there is no reason why an N 2 -fixing organelle could not be maintained in the cell, such organelles have yet to be described ( 51 ). The findings of this study, along with the regulation of spheroid body size ( 17 ) and coevolution of B. bigelowii and UCYN-A ( 53 ), suggest that the evolution of the nitroplast is underway and establish B. bigelowii as an important model system of great interest for understanding organellogenesis, with implications for contemporary efforts to engineer N 2 -fixing capabilities into agricultural plants ( 10 , 57 ).…”
Section: Ucyn-a As a Nitrogen-fixing Organellementioning
confidence: 81%
“…Several presumed endosymbiotic interactions have been described that involve unicellular eukaryotic algae and N 2 -fixing intracellular spheroid bodies that are evolutionarily related to cyanobacteria ( 6 ), including diatom symbionts ( 7 ) and the Candidatus Atelocyanobacterium thalassa (UCYN-A) symbiosis with a haptophyte alga ( 8 ). However, it has remained unclear where these symbiotic relationships fall along the spectrum of endosymbiosis to organelle, and no N 2 -fixing organelle has yet been discovered ( 9 , 10 ).…”
mentioning
confidence: 99%